Moments of Truth / New Strategies for Today's Customer - Driven Economy - Carlzon Jan (Harper Collins Publishers, 1989)
This book is about the importance of responding to a changing marketplace, and offers proof that the search for corporate excellence is neither monopolized by, nor restricted to, American finance and industry. Foreword, A Moment of Truth, The Vingresor and Linje Flyg Turnarounds, The SAS Turnaround, Profession: Leader, Setting the Strategy, Flattening the Pyramid, Taking Risks, Communicating, Boards and Unions, Measuring Results, Rewarding Employees, The Second Wave.